The African Capacity Building Initiative : toward improved policy analysis and development management. - World Bank. (Washington, D.C. : World Bank, 1991)
The African Capacity Building Initiative (ACBI) is aimed at building and strengthening local capacities in policy analysis and development management in Sub-Saharan Africa
Includes bibliographical references (p. 47).
osc 9/09/2021
Loans
Keywords: Management; Africa, Sub-Saharan